Fashion and Textiles International Journal of Interdisciplinary Research - Oh, KyungWha
Fashion and Textiles aims to advance knowledge and to seek new perspectives in the fashion and textiles industry worldwide. We welcome original research articles, reviews, case studies, book reviews and letters to the editor. The scope of the journal includes the following four technical research divisions: Textile Science and Technology: Textile Material Science and Technology; Dyeing and Finishing; Smart and Intelligent Textiles Clothing Science and Technology:  Physiology of Clothing/Textile Products; Protective clothing ; Smart and Intelligent clothing; Sportswear; Mass customization ; Apparel manufacturing Economics of Clothing and Textiles/Fashion Business: Management of the Clothing and Textiles Industry; Merchandising; Retailing; Fashion Marketing; Consumer Behavior; Socio-psychology of Fashion Fashion Design and Cultural Study on Fashion: Aesthetic Aspects of Fashion Product or Design Process; Textiles/Clothing/Fashion Design; Fashion Trend; History of Fashion; Costume or Dress; Fashion Theory; Fashion journalism; Fashion exhibition.